Response of broilers to dietary balanced protein. 2. Determining the optimum economic level of protein - Azevedo, Jefferson Moraes [UNESP]; De Paula Reis, Matheus [UNESP]; Gous, Robert M.; Dorigam, Juliano César De Paula; Lizana, Rony Riveros [UNESP]; Sakomura, Nilva Kazue [UNESP] (CSIRO Publishing, 2021)
Context: Tables of nutrient requirements assist nutritionists to formulate acceptable feeds for broilers but do not consider the objective of a business, namely, to maximise economic returns. Aims: The objective of the present study was to demonstrate that the optimum economic level of balanced protein is not static, but varies according to economic conditions. Methods: Responses of male and female broilers, reported in a companion paper, were used to calculate feed intake and weights of body, carcass, breast, leg and wing at 28, 42 and 56 days of age as functions of dietary balanced protein. Cost of feeding and revenue generated for live, dressed, and further-processed birds were calculated, from which the margin over feeding cost was generated separately for males and females at three ages and three revenue-generating scenarios. Key results: Using baseline values for the cost of protein-containing ingredients and revenue for birds sold live, dressed or further-processed, the dietary protein content that maximised margin over feed cost was always higher for males than for females, and for birds sold further-processed than for those sold dressed or live. Using digestible lysine as the reference amino acid, the optimum in the starter period for males sold live, dressed and further processed was 12.6, 13.3 and 14.2 g lysine/kg respectively. For females, the equivalent values were 11.9, 12.6 and 13.3 g/kg respectively. Where the cost of protein-containing ingredients was increased by 25% or revenue generated from the sale of product was reduced by 25%, the optimum economic level of dietary protein decreased compared with the baseline value. The opposite pertained when ingredient costs decreased, or revenues increased by 25%. Conclusions: These results demonstrated the extent to which economic factors influence the optimum economic level of dietary balanced protein to be fed to broilers. Implications: We have demonstrated that the response of broilers to dietary balanced protein may be used to maximise economic returns of a broiler enterprise under different scenarios.
Keywords: amino acids; economic optimisation; feeding cost; gross margin; revenue